2014
DOI: 10.1016/j.jegh.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The association between disability and cognitive impairment in an elderly Tanzanian population

Abstract: Cognitive impairment is thought to be a major cause of disability worldwide, though data from sub-Saharan Africa (SSA) are sparse. This study aimed to investigate the association between cognitive impairment and disability in a cohort of community-dwelling older adults living in Tanzania. The study cohort of 296 people aged 70years and over was recruited as part of a dementia prevalence study. Subjects were diagnosed as having dementia or mild cognitive impairment according to the DSM-IV criteria. Disability l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Second, cognitive impairment correlated with incontinence may mediate through the functional disability. www.nature.com/scientificreports www.nature.com/scientificreports/ Our research findings were consistent with those of other studies that have found bidirectional relationships between cognitive impairment and functional disability 6,7,23 . Furthermore, a meta-analysis study 24 found that physical functioning was a more consistent predictor of cognitive change than cognitive change was of physical functioning; this is in agreement with the findings of our study because stronger impacts were identified in most models.…”
Section: Discussionsupporting
confidence: 92%
“…Second, cognitive impairment correlated with incontinence may mediate through the functional disability. www.nature.com/scientificreports www.nature.com/scientificreports/ Our research findings were consistent with those of other studies that have found bidirectional relationships between cognitive impairment and functional disability 6,7,23 . Furthermore, a meta-analysis study 24 found that physical functioning was a more consistent predictor of cognitive change than cognitive change was of physical functioning; this is in agreement with the findings of our study because stronger impacts were identified in most models.…”
Section: Discussionsupporting
confidence: 92%
“…As populations age, dementia is becoming increasingly common and is associated with high levels of disability (Prince et al, 2011a;Dotchin et al, 2015;Kisoli et al, 2015). Despite the growing body of epidemiological data, diagnosis of dementia in many parts of SSA can be difficult because of a shortage of specialist physicians (Bower and Zenebe, 2005;Dotchin et al, 2013) and a lack of appropriate screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…Results were in concordance with studies where cognitive deficit was significantly associated with disability in elderly population; global activity limitation and participation restriction. 39,40 Thus, findings of correlations matrix showed age of dementia subjects had positive correlation with BPSD i.e., higher NPI, CMAI scores and WHODAS 2.0 disability scores. Furthermore, dementia severity as delineated by MMSE scores (lower the score, severe the dementia) showed a negative correlation with BPSD on NPI, agitation on CMAI and disability on WHODAS 2.0 i.e., decrease in MMSE score has increase in BPSD, agitation and disability.…”
Section: Discussionmentioning
confidence: 89%